Psychological stress, body shape and cardiovascular events: Results from the Whitehall II study - Kubera, Britta; Kohlmann, Thomas; Peters, Achim (Comprehensive Psychoneuroendocrinology (Online), 2022)
It is known that persistent psychological stress predicts changes in body shape in two different ways: some stressed people lose weight, others gain weight. It is also known that persistent psychological stress predicts adverse health events. But it is unknown what role the body shape plays in this particular network of relationships. We therefore analyzed the Whitehall II dataset to relate body shape to stress and health risk. Data of 4969 men and 2138 women from the Whitehall II cohort were analyzed. Psychological stress (General Health Questionnaire) was measured three times in the years 1991 till 2001. Body shape (BMI, waist and hip circumferences) was measured in the years 1991 till 1994. Childhood adversities were retrospectively assessed by questionnaire. Outcomes included the incidence of non-fatal or fatal CHD events (coronary heart disease) collected up to the years 2012 and 2013 and all-cause mortality collected up to July 2015. Cox proportional hazard models were conducted to estimate the relation between psychological stress and CHD events or all-cause mortality. There was an increase in the expected hazard to develop CHD with high psychological stress (men: Exp (B) = 1.25 (1.06–1.47); P = 0.008; women: Exp (B) = 1.34 (1.05–1.70); P = 0.017). We found a clear dose-response relationship for the association between psychological stress and CHD events in both genders. That is, subjects with consistently high psychological stress in all assessments had a 2.4-fold (men) or 2.3-fold (women) higher risk for later CHD events compared to never-stressed subjects. Moreover, subjects with a high sum score of all 13 childhood experiences had a 10% increased hazard to develop fatal or non-fatal CHD events in adulthood. Although we could not find stress or BMI linked to all-cause mortality, the waist-to-hip ratio contributed to the risk of all-cause mortality in both genders (Exp (B) = 34.66 (6.43–186.92); P < 0.001 for men; Exp (B) = 60.65 (9.33–394.22); P < 0.001 for women). This analysis supports the notion that psychological stress and childhood adversities are associated with the risk of fatal or non-fatal CHD events. When this relationship is analyzed in more detail, the Whitehall II dataset provides further insights into the role of body shape. That is, stress is also related to changes in body shape, with waist size in particular predicting higher all-cause mortality. •We used Whitehall II data and constructed an overall picture of the relations between psychological stress, body shape and adverse health outcomes.•We demonstrated a dose-dependent relationship between psychological stress and the risk of fatal or non-fatal CHD events.•Stress increases the risk of both CHD events and body shape changes, with waist circumference but not BMI increasing the mortality risk.•Body shape –more specifically waist size– is symptomatic of stress and predictive of all-cause mortality.